E-LEADERSHIP AS A BUFFER: MITIGATING THE IMPACT OF TECHNOFERENCE ON WORK-LIFE BALANCE - Sonu; Mehdi, Syed Asif; Srivastava, Priyanka (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the increasingly digital work environment, especially within the IT sector, the intrusion of technology into personal and professional boundaries termed technoference has emerged as a critical factor disrupting work-life balance. This study investigates the impact of technoference on the work-life balance of women employees in the IT industry and examines the mediating role of e-leadership in this relationship. By employing quantitative methods and analysing data through SPSS regression analysis, the study provides empirical evidence that highlights how effective e-leadership can mitigate the adverse effects of technoference. The findings offer valuable insights for organizations seeking to enhance employee well-being and foster supportive leadership practices in remote work settings. The study contributes both to academic literature and practical workforce management by proposing leadership based interventions to help women in the IT sector maintain a healthier balance between work and family responsibilities.